Natural rubber latex used as drug delivery system in guided bone regeneration (GBR) - Herculano,Rondinelli Donizetti (2009)
In this work, we propose natural rubber latex (NRL) membranes as a protein delivery system. For this purpose Bovine Serum Albumin (BSA) was incorporated into the latex solution for in vitro protein delivery experiments. Different polymerization temperatures were used, from -10 to 27 °C, in order to control the membrane morphology. These membranes were characterized by Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), as well as the Lowry Method to measure the BSA release. SEM and AFM microscopy analysis showed that the number, size and distribution of pores in NRL membranes can be varied, as well as its overall morphology. We have found that the morphology of the membrane is the predominant factor for higher protein release, compared with pore size and number of pores. Results demonstrated that the best drug-delivery system was the membrane polymerized at RT (27 °C), which does release 66% of its BSA content for up to 18 days. Our results indicate that NRLb could be used in the future as an active membrane that could accelerate bone healing in GBR.